The Effectiveness of digital technology-based learning models on students' mathematical abilities - Susanti, Ade; Kamid; Syaiful; Huda, Nizlel (Pusat Studi Pengembangan Pembelajaran Matematika, 2026)
ABSTRACT This study aims to analyze the effectiveness of implementing digital technology-based learning models in improving students' mathematical abilities in higher Education through systematic literature review. Mathematical skills are an essential competency needed by students in facing the era of the industrial revolution 4.0. However, data shows that students' mathematical achievement in various countries is still low. This study uses the systematic literature review method with the PRISMA protocol to identify, evaluate, and synthesize 47 research articles from Scopus and Sinta-indexed journals during 2018-2024. The analysis results showed that implementing digital technology-based learning, such as mobile application-assisted learning, adaptive learning systems, augmented reality, and game-based learning, could improve students' mathematical skills with an average effect size of 0.78 (strong influence). Significant findings indicate that personalized learning through adaptive technology substantially improves mathematical problem-solving capabilities. In contrast, immersive technologies such as AR/VR effectively improve conceptual understanding of multivariable geometry and calculus materials. This research contributes in the form of a comprehensive mapping of various digital learning models and their optimal implementation contexts, as well as identifying opportunities for integrating big data and artificial intelligence in creating an adaptive mathematical learning ecosystem. Further research is needed to explore the long-term impact of implementing digital technologies and develop a pedagogical framework that optimizes the synergy between technology and constructivist approaches in mathematical learning in higher Education. Keywords: Learning Model, Digital Technology, Mathematical Ability, Higher Education.